Transition metal pincer catalysts for formic acid dehydrogenation: a mechanistic perspective - Kumar, N. Sai; Adhikary, Anubendu (Frontiers in Chemistry, 2024)
The storage and transportation of hydrogen gas, a non-polluting alternative to carbon-based fuels, have always been challenging due to its extreme flammability. In this regard, formic acid (FA) is a promising liquid organic hydrogen carrier (LOHC), and over the past decades, significant progress has been made in dehydrogenating FA through transition metal catalysis. In this review, our goal is to provide a detailed insight into the existing processes to expose various mechanistic challenges associated with FA dehydrogenation (FAD). Specifically, methodologies catalyzed by pincer-ligated metal complexes were chosen. Pincer ligands are preferred as they provide structural rigidity to the complexes, making the isolation and analysis of reaction intermediates less challenging and consequently providing a better mechanistic understanding. In this perspective, the catalytic activity of the reported pincer complexes in FAD was overviewed, and more importantly, the catalytic cycles were examined in detail. Further attention was given to the structural modifications, role of additives, reaction medium, and their crucial effects on the outcome.